Forgiveness Therapy to Enhance Posttraumatic Growth in Individuals with Adverse Childhood Experiences - Aditya, Dita Permata; Utami, Muhana Sofiati (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2025)
Adverse childhood experiences (ACEs) can lead to posttraumatic stress and disruptions in adulthood, highlighting the need for appropriate treatment. This study aimed to examine the effect of Forgiveness Therapy in improving posttraumatic growth (PTG) among young adults with ACEs history. A partially randomized experimental design with pretest, posttest 1, and posttest 2 was implemented. The study included 16 participants who were divided into two groups with eight participants, respectively. Statistical analysis using repeated measures ANOVA indicated interaction between PTG scores with group (F(2) = 19.0, p < 0.01). An independent sample t-test also revealed a significant difference of PTG score between groups, with a large effect size (t(14,0)= 2.38; d= 1.19). In conclusion, Forgiveness Therapy was found to increase PTG by facilitating emotional regulation, cognitive reframing, self-disclosure, and the therapeutic effects of group therapy.